The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5430/wjel.v13n8p288
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Learning Atmosphere through Process Drama: Teaching English Parts-of-Speech (PoS) in Indian Classroom

Pratik Kumar Mahant,
Sohaib Alam,
Sanjukta Ghosh
et al.

Abstract: This paper investigates the effectiveness of process drama in teaching English parts-of-speech to middle school students in an eastern Indian school. For the application part, researchers developed process drama-based lesson plans following the structural approach and implemented them among the students of class VII studying English as a second language (L2). The study employed a quasi-experimental design, with a pretest-posttest approach to data collection. Additionally, the facilitator consistently took obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
“…These observations underscore the role of the learner's first language in inflectional morpheme error patterns in ESL contexts. Moreover, numerous research supports the idea of using different sorts of practical eclectic praxis can be used to curtail errors of students in real life contexts (Alam et al, 2022;Alam et al, 2020;Alam, 2022;Alam, 2023;Mahant et al, 2023). Productive skills of language like writing needs real life practice which can only be provided through communicative strategies or activities that can provides platforms to students to practice language skills .…”
Section: Discussionmentioning
confidence: 99%
“…As Sarah Eaton says "there is no longer focus on grammar and memorization but rather using language and cultural knowledge as a means to communicate and connect to others around the globe" (p. 5, 2010). Moreover, recent studies, such as Mahant et al (2023), have showcased the efficacy of Process drama in the language classroom, where they experimented with the approach of teaching parts of speech to students. The Alam, Karim, and Ahmad study (2020) also highlighted some critical aspects of PD, and they devised some practical activities for classroom pedagogy that can be further improvised according to the nature of the individual classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By assuming different roles and engaging in dramatic activities, participants are able to explore and understand various perspectives, emotions, and responses within a safe and supportive environment. This experiential learning approach allows individuals to develop empathy, critical thinking, and communication skills, as well as gain a deeper understanding of complex social and personal issues (Mahant et al, 2023).…”
Section: Introductionmentioning
confidence: 99%